Edukasi Pencegahan Preeklamsia pada Ibu Hamil - Sultina Sarita; Arsulfa Arsulfa; Syahrianti Syahrianti; Hendra Yulita; Muliati Dolofu; Hesti Resyana (PT Karya Inovasi Berkelanjutan, 2025)
Preeclampsia remains one of the leading causes of maternal morbidity and mortality in Indonesia. Preventive efforts can be implemented through educational interventions aimed at increasing awareness of the early signs of preeclampsia. This activity aimed to improve pregnant women’s knowledge of preeclampsia through health education conducted in the form of counseling sessions, interactive discussions, leaflet distribution, and knowledge evaluation using pre-test and post-test assessments. The activity was carried out in the working area of Abeli Community Health Center, Abeli District, Kendari City, involving 15 pregnant women as participants. The program stages included coordination with health center staff, assessment of vital signs (blood pressure and body weight), completion of pre-test questionnaires, delivery of educational materials, distribution of informational leaflets, interactive discussions, and evaluation through post-test questionnaires. The results demonstrated an increase in participants’ knowledge regarding the signs and symptoms of preeclampsia after participating in the educational activity. The practical implication of this program is that health education combined with basic health screening serves as a preventive strategy to enhance pregnant women’s awareness of the signs and symptoms of preeclampsia and encourages regular antenatal care visits through community-based services such as Posyandu. It is important to note that recent evidence indicates that the identification of preeclampsia is no longer based solely on the classical triad of hypertension, edema, and proteinuria, but rather emphasizes early indicators such as elevated blood pressure assessed through mean arterial pressure and increased body mass index. These assessments can be conducted from the preconception period through routine antenatal care visits. Contribution to the Sustainable Development Goals (SDGs) This educational program on preeclampsia prevention among pregnant women contributes to Sustainable Development Goal (SDG) 3: Ensure healthy lives and promote well-being for all at all ages. Specifically, it supports Target 3.1, which aims to reduce the global maternal mortality ratio through effective prevention and early detection of pregnancy-related complications. By improving pregnant women’s knowledge of the early signs and risk factors of preeclampsia through health education and basic health screening, this program strengthens preventive maternal health services and promotes timely antenatal care utilization. Ultimately, the intervention supports the enhancement of maternal health awareness and contributes to safer pregnancy outcomes at the community level.